2014
DOI: 10.1039/c3dt52546e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid synthesis of iron 1,4-naphthalenedicarboxylate by microwave irradiation with enhanced gas sorption

Abstract: A high quality crystalline porous coordination polymer (PCP), Fe(OH)(1,4-NDC)·2H2O (1,4-NDC = 1,4-naphthalenedicarboxylate), was successfully prepared using a rapid and efficient microwave irradiation method (hereafter termed M-PCP-Fe). It was noteworthy that the microwave irradiation method reduced the reaction time considerably to 1 min, while it took three days for the conventional hydrothermal method to prepare non-uniform crystal morphologies in a one-pot manner (hereafter termed H-PCP-Fe). The effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Lu et al performed this synthesis as well, and showed that microwave assisted M-MOF-5 had a higher adsorption capacity than MOF-5 produced using standard techniques, although they were not able to achieve the very high Langmuir surface areas and adsorption capacities of Choi et al [29]. Currently one of the best MOF adsorbents, M/DOBDC series with Ni and Mg metal sites, have also been prepared by microwave synthesis by Wu et its conventional hydrothermal synthesis and also observed much smaller and more uniform crystals with 15 µm in length and 3.0 µm in width [37]. The crystallization temperature was found to be slightly lower than 120 °C under microwave irradiation compared to 150 °C under hydrothermal conditions.…”
Section: Microwave Synthesismentioning
confidence: 91%
See 2 more Smart Citations
“…Lu et al performed this synthesis as well, and showed that microwave assisted M-MOF-5 had a higher adsorption capacity than MOF-5 produced using standard techniques, although they were not able to achieve the very high Langmuir surface areas and adsorption capacities of Choi et al [29]. Currently one of the best MOF adsorbents, M/DOBDC series with Ni and Mg metal sites, have also been prepared by microwave synthesis by Wu et its conventional hydrothermal synthesis and also observed much smaller and more uniform crystals with 15 µm in length and 3.0 µm in width [37]. The crystallization temperature was found to be slightly lower than 120 °C under microwave irradiation compared to 150 °C under hydrothermal conditions.…”
Section: Microwave Synthesismentioning
confidence: 91%
“…The crystallization temperature was found to be slightly lower than 120 °C under microwave irradiation compared to 150 °C under hydrothermal conditions. In addition, CO 2 capacity uptake was higher with the crystals obtained via microwave synthesis possibly due to the smaller sized crystals, which it is proposed may contribute to a higher potential for adsorbate access to the free volume of the framework [37]. Enhanced CO 2 capture capacity was also observed in CPM-5 made via microwave synthesis with BET surface area of 2187 m 2 /g which was dramatically higher than 580 m 2 /g for CPM-5 crystals made via conventional synthetic routes [38].…”
Section: Microwave Synthesismentioning
confidence: 92%
See 1 more Smart Citation
“…The kinetic parameters for compounds 1 and 4 were calculated for the first step according to the above two methods (4,5) and are cited in Table 7. The thermodynamic parameters, entropy (DS*), enthalpy(DH*)and free energy(DG*) for the two complexes were computed Table 8 using the following equations X-ray Powder Diffraction of the Coordination Polymer 1, 1m, 1s…”
Section: Thermal Analysismentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are currently receiving great interest due to their vast potential applications in a variety of technical areas such as gas storage [1][2][3][4][5], separation process [6][7][8], drug delivery [9,10], catalysis [11][12][13][14][15][16] and molecular sensing [17][18][19]. Organic ligands, carboxylates and pyridyls have been good candidates because they have outstanding ligating to metal ions and readily adjustable length and geometry.…”
Section: Introductionmentioning
confidence: 99%